The friendship-enmity relationship deconstruction: truth and women. Considering the book Thus spoke Zarathustra by Nietzsche - Lastra Gutiérrez, Pedro (Resonancias. Revista de Filosofía, 2020)
It is often claimed without further study that Nietzsche is a misogynist philosopher. This is due to the controversial and failed relationships of friendship and love he had with family and friends, which has helped to interpret some paragraphs of the first book of Thus Spoke Zarastustra as a catharsis and an attack on women and what they represent. In the present article we will make a brief genealogical analysis of the chapter called “On my honour, my friend”, elucidating in a deconstructive manner the and purpose of the author regarding truth, woman and friendship, recognizing in his writing an attempt to break with the principles of rationality that sustain the basic dualism around the female figure imposed from a heteropatriarchal order.